Molecular Photovoltaics in Nanoscale Dimension - Burtman, Vladimir (Molecular Diversity Preservation International (MDPI), 2011)
This review focuses on the intrinsic charge transport in organic photovoltaic (PVC) devices and field-effect transistors (SAM-OFETs) fabricated by vapor phase molecular self-assembly (VP-SAM) method. The dynamics of charge transport are determined and used to clarify a transport mechanism. The 1,4,5,8-naphthalene-tetracarboxylic diphenylimide (NTCDI) SAM devices provide a useful tool to study the fundamentals of polaronic transport at organic surfaces and to discuss the performance of organic photovoltaic devices in nanoscale. Time-resolved photovoltaic studies allow us to separate the charge annihilation kinetics in the conductive NTCDI channel from the overall charge kinetic in a SAM-OFET device. It has been demonstrated that tuning of the type of conductivity in NTCDI SAM-OFET devices is possible by changing Si substrate doping. Our study of the polaron charge transfer in organic materials proposes that a cation-radical exchange (redox) mechanism is the major transport mechanism in the studied SAM-PVC devices. The role and contribution of the transport through delocalized states of redox active surface molecular aggregates of NTCDI are exposed and investigated. This example of technological development is used to highlight the significance of future technological development of nanotechnologies and to appreciate a structure-property paradigm in organic nanostructures.